ANALISIS MURID DALAM PELAJARAN DESIGN DENGAN MENGGUNAKAN NAÃVE BAYES - Pangaribuan, Jefri Junifer; Ferawaty, Ferawaty (Politeknik Ganesha Medan, 2021)
Students' interest in a field is usually seen from the grades resulting from students' learning in the classroom. This is a common thing for parents and teachers to do. In the research conducted by researchers this time is in the field of design studied by students in the classroom in one semester, namely the subjects Photoshop and CorelDraw. The grades taken are grades that include the value of theory, practical grades, assignments, and quiz assignments obtained by students in the classroom. The four grades will be calculated until they get a provision on whether or not the student graduates in the subject. These values will be studied by researchers using the NaÃ¯ve Bayes method, so that it can be known how much can be said to pass in this design lesson. Researchers conducted research using Rapid Miner program, where the data will be divided into 2 parts, namely by using some existing data as learning samples and the rest as test data. The results obtained from the experiment were 146 students graduated in the field of design, and 119 students failed. This suggests the experiment using the NaÃ¯ve Bayes method was successful if the experiment data was entered a lot